Assessment of potential drug interactions by characterization of human drug metabolism pathways using non‐invasive bile sampling. (10th January 2013) - Bloomer, Jackie C.; Nash, Mike; Webb, Alison; Miller, Bruce E.; Lazaar, Aili L.; Beaumont, Claire; Guiney, William J.
<x xml:space="preserve">Abstract</x> Aim Characterization of the biliary disposition of GSK1325756, using a non‐invasive bile sampling technique and spectrometric analyses, to inform the major routes of metabolic elimination and to enable an assessment of victim drug interaction risk. Method Sixteen healthy, elderly subjects underwent non‐invasive bile capture using a peroral string device (Entero‐Test®) prior to and following a single oral dose of GSK1325756 (100 mg). The device was swallowed by each subject and once the weighted string was judged to have reached the duodenum, gallbladder contraction was stimulated in order to release bile. The string was then retrieved via the mouth and bile samples were analyzed for drug‐related material using spectrometric and spectroscopic techniques following solvent extraction. Results Nuclear magnetic resonance spectroscopy (NMR) indicated that the O‐glucuronide metabolite was the major metabolite of GSK1325756, representing approximately 80% of drug‐related material in bile. As bile is the major clearance route for GSK1325756 (only 4% of the administered dose was excreted in human urine), this result indicates that uridine 5'‐diphospho‐glucuronosyltransferases (UGTs) are the major drug metabolizing enzymes responsible for drug clearance. The relatively minor contribution made by oxidative routes reduces the concern of CYP‐mediated victim drug interactions. Conclusion The results from this study demonstrate the utility of deploying the Entero‐Test® in early human studies to provide information on the biliary disposition of drugs and their metabolites. This technique can be readily applied in early clinical development studies to provide information on the risk of interactions for drugs that are metabolized and eliminated in bile.